2020
DOI: 10.1177/0268355520947610
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of pelvic venous insufficiency in patients with postural orthostatic tachycardia syndrome

Abstract: Objectives Some patients with postural orthostatic tachycardia syndrome (POTS) demonstrate improved dysautonomic symptoms following treatment for pelvic venous insufficiency (PVI). This study assessed the prevalence of significant left common iliac vein (LCIV) compression in POTS patients. Methods Radiologists retrospectively reviewed CT images of pelvic veins for 216 women (191 with POTS and 25 age-comparable controls).Quantitative vascular analysis identified percent-diameter compression of the LCIV by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Common comorbidities of POTS are mast cell activation syndrome (MCAS), Ehlers-Danlos syndrome, sensory neuropathy, venous compression syndromes, and autoimmune disorders such as Sjögren's syndrome, Hashimoto's thyroiditis, rheumatoid arthritis, and celiac disease. 5 , 9 , 11 , 14 , 15…”
Section: Introductionmentioning
confidence: 99%
“…Common comorbidities of POTS are mast cell activation syndrome (MCAS), Ehlers-Danlos syndrome, sensory neuropathy, venous compression syndromes, and autoimmune disorders such as Sjögren's syndrome, Hashimoto's thyroiditis, rheumatoid arthritis, and celiac disease. 5 , 9 , 11 , 14 , 15…”
Section: Introductionmentioning
confidence: 99%
“…Following successful LCIV stenting, two patients’ POTS symptoms and quality of life significantly improved, paralleling Knuttinen et al .’s 9 finding that LCIV stenting significantly alleviated dysautonomia symptoms in patients with POTS and MTS. Their study, however, did not characterize the presence of EDS.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, MTS may exacerbate the common POTS symptoms of hypovolemia and lower extremity venous pooling by decreasing venous return. 9 Coupling reduced venous return with the resulting changes in blood flow when standing up, patients with POTS experience decreased venous return, leading to sympathetic hyperactivation, orthostatic intolerance, baroreceptor inactivation, and tachycardia. 9 Left common iliac vein stenting can mitigate these symptoms by decreasing lower extremity venous pooling and subsequently improve downstream sympathetic nervous system hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive hypothesis to explain the comorbid factors is that connective tissue laxity in vessel walls predisposes individuals to increased venous pooling in dependent vessels, and reduced return of blood to the heart, thereby contributing to orthostatic intolerance 15,17,[24][25][26]28 and in fact a recent study showed an increased prevalence of pelvic vein abnormalities in patients with the postural tachycardia syndrome. 33 Joint laxity has also been linked to "myofascial pelvic pain." 34 In all, results of this internet survey are most supportive of Taylor's 1949 description of the "congestionfibrosis syndrome."…”
Section: Discussionmentioning
confidence: 99%